THE EFFECT OF PROJECT BASED LEARNING ON MIDDLE SCHOOL STUDENTS WRITING ABILITY IN SMP IT DAARUL ISTIQLAL MARINDAL I - Fajar Aldiansyah; Utami Dewi (Universitas Kuningan, 2024)
This study examines the impact of Project-Based Learning (PBL) on middle school students' writing abilities. Writing proficiency is a crucial skill, yet traditional methods often fall short in engaging students and providing authentic contexts for practice. The objective of this research is to investigate whether PBL can effectively enhance students' writing skills. Using a quantitative approach, a pre-test and post-test experimental design was employed, involving 42 students at SMP IT Daarul Istiqlal Marindal I. The participants were divided into experimental and control groups, with the experimental group taught using PBL and the control group using traditional methods. Data collection included pre-tests and post-tests, with statistical analysis conducted using SPSS for normality, homogeneity, reliability, T-tests, and ANOVA. The results demonstrated that PBL significantly improved students' writing abilities, as evidenced by higher post-test scores in the experimental group compared to the control group. These findings suggest that PBL is an effective instructional methodology for enhancing writing proficiency, providing authentic contexts for practicing writing skills, and increasing student engagement and motivation. Keywords: Project-Based Learning, writing abilities, experimental design, instructional methodology, student engagement.